Ethical boundary work in citizen science - Dick Kasperowski (Nordic Journal of Science and Technology Studies, 2021)
The concept of boundary work (Gieryn 1983, 1999) has been developed to capture the ways in which scientists collectively defend and demarcate their intellectual territories. This article applies the concept of boundary work to the ethical realm and investigates the ethical boundary work performed by researchers in the field of citizen science (CS) through a literature review and by analysing accounts of ethics presented in CS literature. Results show that ethical boundary work in the CS literature is, to a large extent, a matter of managing ambiguities and paradoxes without any clear boundaries drawn between the unethical and ethical. Scientists are negotiating ethical positions, which might, occasionally, enhance the ethical authority of ‘non-science’ and non-scientists, as well as maintain already established research ethics. The main ethical boundary work in CS displays variations towards perceived insufficiencies of conventional research ethics to accommodate “outsiders”, addressing issues of distribution, relevance, and expulsion as science include volunteer contributors in the scientific process.